2018
DOI: 10.13057/biodiv/d200109
|View full text |Cite
|
Sign up to set email alerts
|

Expression of oil palm (Elaeis guineensis) polyisoprenoids in response to Ganoderma boninense infection

Abstract: Afandi D, Basyuni M, Putri LAP, Chalil D, Syahputra I. 2019. Expression of oil palm (Elaeis guineensis) polyisoprenoids in response to Ganoderma boninense infection. Biodiversitas 20: 68-76. Currently, oil palm is an important economic crop and has become one of the world's major vegetable oils as well as a potential source of biodiesel. Unfortunately, oil palm plantations in Asia, particularly in Indonesia and Malaysia face the threat of basal stem root diseases caused by Ganoderma sp. Various methods and app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
9
0
3
Order By: Relevance
“…Although studies related to the biological activity of polyprenol and dolichol are still limited, in general, the results of the study explain that these two secondary metabolite compounds are involved in plant defense mechanisms against abiotic and biotic stress (Basyuni et al 2017a;Baczewska et al 2014). Afandi et al (2019) reported that there was a different expression of polyisoprenoid profiles concerning the level of plant resistance to Ganoderma boninense attack. This difference in expression is also related to its presence in different tissues, treatments, and tolerance levels of plants.…”
Section: Carbon Chain Length Analysismentioning
confidence: 92%
“…Although studies related to the biological activity of polyprenol and dolichol are still limited, in general, the results of the study explain that these two secondary metabolite compounds are involved in plant defense mechanisms against abiotic and biotic stress (Basyuni et al 2017a;Baczewska et al 2014). Afandi et al (2019) reported that there was a different expression of polyisoprenoid profiles concerning the level of plant resistance to Ganoderma boninense attack. This difference in expression is also related to its presence in different tissues, treatments, and tolerance levels of plants.…”
Section: Carbon Chain Length Analysismentioning
confidence: 92%
“…The DNA band profile resulted by all different markers have measured the intensity of bands (as a predicted expression) using Gel Analyzer 2010 and scored according to above of average as (1) and below-average as (0) to collect a binary matrix to put on cluster analysis (Afandi et al 2018).…”
Section: Dna Intensity Analysismentioning
confidence: 99%
“…The present study supported the previous reports (Afandi et al 2018) that molecular markers to be considered as promising markers for G. boninense resistance screening oil palm. In addition to the polyisoprenoid pattern in E. guineensis as a potential biochemical marker in response to G. boninense infection (Afandi et al 2019). Table 3 shows the microsatellite for the population of G. boninense isolates.…”
Section: Selection Of Polymorphism Markermentioning
confidence: 99%
“…Recently molecular performances showing the grouping of plant resistance to G. boninense occurred in healthy leaves of mature oil palm (Afandi et al 2018). Furthermore, polyisoprenoid carbon chain-length has been shown to be a chemotaxonomic marker for the screening of oil palm resistance to G. boninense (Afandi et al 2019. Therefore, a study on genetic diversity and structure of G. boninense is needed in order to formulate improved control strategies for this disease.…”
Section: Introductionmentioning
confidence: 99%